Design and Stability Evaluation of Active Peptides from Indonesian Echinozoa as Acetylcholinesterase (AChE) Inhibitors for Alzheimer’s Therapy - Laelatul Afifah; Vania Uly Andyra; Marlyn Dian Laksitorini; Tri Rini Nuringtyas (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Alzheimer’s disease is characterized by cognitive decline resulting from decreased acetylcholine (ACh) levels due to excessive acetylcholinesterase (AChE) activity. Current therapies, such as galantamine, have several side effects. Bioactive peptides derived from marine Echinozoa (sea urchins and sea cucumbers) have emerged as promising therapeutic agents owing to their structural diversity and diverse bioactivities. Previous studies identified peptides from sea cucumbers and sea urchins collected along the southern coast of Gunung Kidul, Yogyakarta (VLCAGDLR, SWIGLK, MNGKKITVRPR, and KTKDLK), which exhibit acetylcholinesterase (AChE) inhibitory activity. However, the therapeutic use of these peptides is challenged by blood–brain barrier (BBB) penetration and stability issues. Therefore, this study was conducted to identify candidate peptides through in silico analysis and to evaluate their stability in phosphate-buffered saline (PBS) as potential AChE inhibitors.METHODS: Molecular docking was conducted to evaluate peptide binding affinity to the active site. The best candidate peptides were synthesized and tested in vitro for AChE inhibition using a colorimetric method. Stability was assessed in PBS by monitoring aggregation through turbidity and Congo Red assays.RESULTS: The sea cucumber peptide SWIGLK showed strong binding affinity (–10.2 kcal/mol) and 12.11% inhibition at 0.19 mM, while the sea urchin peptide KTKDLK exhibited –8.2 kcal/mol and 11.50% inhibition at 0.19 mM. Both peptides remained stable in PBS without aggregation for up to 48 h.CONCLUSION: SWIGLK and KTKDLK demonstrate the most significant AChE inhibitory activity and maintained structural stability, hence supporting their potential as peptide-based candidates for Alzheimer’s therapy.KEYWORDS: Alzheimer, AChE inhibitor, holothuroidea, echinoidea, bioactive peptide, peptide stability